Metallo-supramolecular materials based on terpyridine-functionalized polyhedral silsesquioxane - Koytepe, Sueleyman; Demirel, Maruf Hursit; Gultek, Ahmet; Seckin, Turgay (Wiley, 2014)
In this study, novel metallo-supramolecular materials based on terpyridine-functionalized polyhedral silsesquioxane were synthesized from 4 '-chloro-2,2 ':6 ',2 ''-terpyridine and amino-group-functionalized polyhedral oligomeric silsesquioxane. The obtained terpyridine-functionalized polyhedral silsesquioxanes were converted to metallo-supramolecular hybrid materials by coordination polycondensation reaction with Co(II) or Cu(II) ions. The supramolecular polymers created were characterized by means of structure, morphology and stimuli-responsive performance employing scanning electron microscopy, amperometric techniques and UV-visible and Fourier transform IR spectroscopy. UV-visible and cyclic voltammetry studies showed that both the optical and electrochemical properties of metallo-supramolecular materials are affected by the substituent at the pyridine periphery. The supramolecular polymers obtained exhibited electrochromism during the oxidation processes of cyclic voltammogram studies. As a result, these terpyridine-functionalized polyhedral silsesquioxanes are good candidates for electronic, opto-electronic and photovoltaic applications as smart stimuli-responsive materials. (c) 2013 Society of Chemical Industry
Keywords: terpyridine ligands; POSS; supramolecular polymers; stimuli-responsive polymers; coordination chemistry